2016
DOI: 10.1021/acsomega.6b00140
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Synthesis of Anisotropic Gold Nanostructures by Bioinspired Cysteine-Containing Peptides

Abstract: In the present study, alkaline peptides AAAXCX (X = lysine or arginine residues) were designed based on the conserved motif of the enzyme thioredoxin and used for the synthesis of gold nanoparticles (GNPs) in the pH range of 2–11. These peptides were compared with free cysteine, the counterpart acidic peptides AAAECE and γ-ECG (glutathione), and the neutral peptide AAAACA. The objective was to investigate the effect of the amino acids neighboring a cysteine residue on the pH-dependent synthesis of gold nanocry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Generally, the interaction of gold atoms with protonated and deprotonated amino acid residues do not differ greatly, which is in agreement with the experimental evidences that gold cluster synthesis occurs in a wide range of pH. 24,67 The fact that deprotonated cysteine has the highest binding energy with both Au 2 and Au + among all the amino acids explains the ne synthesis of gold nanoclusters on thiolates. 68,69 Our results suggest that binding energy between neutral silver clusters and DNA is rather weak (DG is equal to À1 to À9 kcal mol À1 ) as compared to charged particles (À55 to À63 kcal mol À1 ).…”
Section: Resultssupporting
confidence: 81%
“…Generally, the interaction of gold atoms with protonated and deprotonated amino acid residues do not differ greatly, which is in agreement with the experimental evidences that gold cluster synthesis occurs in a wide range of pH. 24,67 The fact that deprotonated cysteine has the highest binding energy with both Au 2 and Au + among all the amino acids explains the ne synthesis of gold nanoclusters on thiolates. 68,69 Our results suggest that binding energy between neutral silver clusters and DNA is rather weak (DG is equal to À1 to À9 kcal mol À1 ) as compared to charged particles (À55 to À63 kcal mol À1 ).…”
Section: Resultssupporting
confidence: 81%
“…In the crystalline growth process of metallic nanoparticles, functional groups of proteins and peptides have specific affinity for certain metallic facets. Thus, proteins and peptides direct the crystalline growth of the nanostructures to a diversity of size and shape (Tofanello et al 2016). Proteins, and peptides are also largely used for the stabilization and functionalization of a diversity of nanostructured materials providing properties such as biocompatibility, plasmonenhanced catalysis, sensing, fabrication of micro/ nanomotors and others.…”
Section: Characteristic Of Protein and Peptide Structures Useful For The Synthesis And Stabilization Of Nanostructuresmentioning
confidence: 99%
“…The mechanism characterizes the existence of competition among Pd ions and FAD for the reduction in such a way that formic acid was necessary as a co-adjuvant reducing agent for the PdNP growing. In another study, Tofanello et al demonstrated that not only the presence of cysteine residues in a peptide structure is the warranty of an adequate reducing capacity for the synthesis of gold nanoparticles (GNPs) (Tofanello et al 2016).…”
Section: Characteristic Of Protein and Peptide Structures Useful For The Synthesis And Stabilization Of Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface functionalization of gold nanoparticles has opened new frontiers for the delivery of drugs such as anticancer and antimicrobial drugs as well as functional studies of biomolecules such as enzymes and antibodies [3][4][5][6]. GNPs can also be synthesized by one-pot, rapid processes, including the in-situ synthesis using the organic functionalizing agent as the reducing compound to convert gold ions (Au 3+ ) to the metallic form [7][8][9]. A diversity of biomolecules and their mimetics has been used for in-situ synthesis of GNPs, but the use of proteins is particularly attractive because these biomolecules act as a template and reducing agents for GNP fabrication [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%